Confessions on the 7:45 : a novel - Unger, Lisa, 1970- (Park Row Books, 2020)
"Be careful to whom you tell your darkest secrets. Selena Murphy is commuting home from her job in the city when the train stalls out on the tracks. She strikes up a conversation with a beautiful stranger in the next seat, and their connection is fast and easy. The woman introduces herself as Martha and confesses that she's been stuck in an affair with her boss. Selena, in turn, confesses that she suspects her husband is sleeping with the nanny. When the train arrives at Selena's station, the two women part ways, presumably never to meet again. But days later, Selena's nanny disappears. Soon Selena finds her once-perfect life upended. As she is pulled into the mystery of the missing nanny, and as the fractures in her marriage grow deeper, Selena begins to wonder, who was Martha really? But she is hardly prepared for what she'll discover."